Desain Sistem Otomasi Jalan Tol = Freeway A Litomation System Design - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT So far, each vehicle passing along a freeway has to stop at the entrance gate to pay the freeway fare, in cash or using customer card as well. Such condition sometimes causes traffic jam at the gate. The situation can be settled if the transaction process of paying the freeway fare can be automated so that the vehicle needs not stop in the gate. To achieve that condition: 1) the payment of the freeway fare is done using bill mechanism 2) the recording process of vehicles' data does not force the vehicles to stop. Two things related to freeway automation system are the data collection and the data processing. This thesis discusses the data design and data processing needed to develop a freeway automation system. Based on the experiment results, it can be seen that the time taken for automatically processing data of a vehicle running into freeway is much less compared to the interarrival time of two vehicles. In the implementation, automation system for freeway requires accurate data of the vehicles and the ownership of the vehicles, so that the wrong claim of bill will never happen. However, a manual system must be kept available to anticipate the breaking down or malfunction of the automatic system.